Swedish-Finnish glossary: disputation words - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish - Finnish glossary of words relating to disputations. Published in Kieliviesti 2/2011. Contains approximately 60 words. 2011.

Swedish - Finnish glossary of words relating to disputations. Published in Kieliviesti 2/2011. Contains approximately 60 entries. 2011.

Svensk-sverigefinsk ordlista med disputationsord. Publicerades i Kieliviesti 2/2011. Innehåller ca 60 ord. 2011.
Svensk-finsk ordlista: disputationsord
Keywords: language of instruction; undervisningsspråk; languages used at work; språk som används på arbetsplatsen; Academic Dissertations as Topic; Akademiska avhandlingar som ämne; Research; Forskning; Academic Dissertation; Akademiska avhandling [Publikationstyp]; scientific research; vetenskaplig forskning; word list; ordlista; Higher and further education; Gymnasial och högre utbildning; Language and linguistics; Språk och lingvistik; Educational Sciences; Utbildningsvetenskap; Languages and Literature; Språk och litteratur